KESALAHAN PELAFALAN DALAM INTERAKSI PEMBELAJARAN BAHASA INDONESIA OLEH SISWA KELAS VIII-A SMP NEGERI 2 TELUK DALAM - Emiliana Aviyanti Duha (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
The problem in this research is that students’ pronouncition errors in pronouncing or enunciating each word when interacting in Indonesian language learning are stillrelatively poor. The aim of this research is 1) to describe the forms of pronounciation errors in Indonesian language learning interactins by clas VIII-A SMP Negeri 2 Teluk Dalam and 2) to describe the causes of pronounciation errors in Indonesian language learning interactions by class VIII-A SMP Negeri 2 Teluk Dalam. This type of research is primary data. Primary data is data obtained directly by researchers from sources, in the form of students pronounciation errors. the data source in this research was 27 students in class VIII-A SMP Negeri 2 Teluk Dalam. The data collection technique in this research is the recording technique. Recording technique is data collection technique by recording student conversations. There are three parts to the data analysis, namely 1) data reduction, 2) data display, and 3) Drawing conclusion. The results of this research are that students still often make pronounciation errors, phoneme addition, intonation errors/words fragments, and pausing errors. The reasons are due to the influence of regional languages, lack of knowledge about linguistics, and being influenced by the  state or condition of speaking apparatus. The suggestion put forward by researchers is that a teacher should always teach and apply good and correct Indonesian language methods when interacting with theachers and classmates during learning.